Religious Experiences Are Interpreted through Priors from Cultural Frameworks Supported by Imaginative Capacity Rather Than Special Cognition - Mulukom, Valerie van (Journal for the cognitive science of religion, 2019)
In this commentary of McCauley and Graham’s book on mental abnormalities and religions, we identify a number of challenges, and present possible extensions of their proposed research. Specifically, we argue that no specialized religious cognition should be assumed, and instead suggest that the cases of mental abnormalities discussed in the book specify particular instances of religious content, and that other disorders may show a more causal relationship to religiosity. We argue that the discussed religious content may be best explained in the context of cultural frameworks and their contribution to experiencing the world through priors and predictive processing. Moreover, cognition required to understand and engage with religion, but not special to it, might crucially involve our capacity for imagination, supported by memory. Disorders in imagination are therefore expected to show likewise dysfunctions in religious phenomena.